More Than Just Pulling Weeds : A Case Study of Engaging Upper-Division Conservation Biology Students in Service-Learning - Tucker , Kimberly Pause; Moran , Christine E. (Experiential Learning and Teaching in Higher Education, 2022)
The field of conservation biology focuses on maintaining biodiversity by mitigating both global and local threats. One of the top threats to biodiversity is the worldwide problem of invasive species. Each community has its own pests to control, and students can engage with this global issue on a local scale through well-designed service-learning courses. This article discusses how students engaged with conservation biology through an integrated service-learning project tackling invasive species at a local nature center. Products of the class, data from class artifacts, as well as student feedback on evaluations are also presented.